Kebijakan Penerapan Tindak Pidana Penistaan Agama Di Indonesia - I Gede Widhiana Suarda; Ainul Azizah; Ahmad Fahrudin (Pusat Riset dan Inovasi Nasional, 2023)
Ethnicity, religion, race and intergroup (SARA) are social elements that have an important role in human life, therefore, the freedom of each party must be respected and guaranteed. Religion is an important element of human existence and perhaps the most impressive element that can exert an important influence on the behavior of individuals. Indonesian positive law regulates punishment for perpetrators of religious blasphemy regulated in Article 156a of the Criminal Code. The initial purpose of enacting this article was against the backdrop of the many sects of belief and mysticism teachings that were considered heretical and not in accordance with the religious teachings of the Indonesian people. Article 156a of the Criminal Code is intended to prevent religious teachings from being distorted which are considered as the main teachings by the leaders or religious leaders concerned; and this rule protects religious peace in society and maintains the values of religious teachings that are maintained by the community from insults/humiliations and from teachings not to embrace a religion based on Belief in the One Supreme God.